2012
DOI: 10.1039/c2ob06833h
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted synthesis of small molecules targeting the infectious diseases tuberculosis, HIV/AIDS, malaria and hepatitis C

Abstract: The unique properties of microwave in situ heating offer unparalleled opportunities for medicinal chemists to speed up lead optimisation processes in early drug discovery. The technology is ideal for small-scale discovery chemistry because it allows full reaction control, short reaction times, high safety and rapid feedback. To illustrate these advantages, we herein describe applications and approaches in the synthesis of small molecules to combat four of the most prevalent infectious diseases; tuberculosis, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 158 publications
0
39
0
Order By: Relevance
“…The development of isoform--selective PLD inhibitors, specifically PLD2--selective inhibitors, may lead to a new class of cancer therapeutics. The authors reported the results of a matrix library approach to increasing PLD2 potency and selectivity within the 1,3,8--triazaspiro-- [4,5]decan--4--one series. All library members were evaluated for their ability to inhibit PLD1 and PLD2 in cellular and biochemical assays with recombinant PLD1 and PLD2 enzymes.…”
Section: Drugs For Central Nervous Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of isoform--selective PLD inhibitors, specifically PLD2--selective inhibitors, may lead to a new class of cancer therapeutics. The authors reported the results of a matrix library approach to increasing PLD2 potency and selectivity within the 1,3,8--triazaspiro-- [4,5]decan--4--one series. All library members were evaluated for their ability to inhibit PLD1 and PLD2 in cellular and biochemical assays with recombinant PLD1 and PLD2 enzymes.…”
Section: Drugs For Central Nervous Diseasesmentioning
confidence: 99%
“…Results show that the installation of an unsaturated heterocycle on the 2--phenyl group of the benzimidazole core proved to be another viable strategy for developing potent and orally efficacious PARP--1 inhibitors. Lavieri et al77 focused on the functionalisation of the 1,3,8--triazaspiro [4,5]decan--4--one scaffold with various halogens. In these syntheses, the closing of the spirocycli five--membered ring meant forcing MW conditions at 150 C for 15 min in AcOH (single mode Biotage Initiator--60), followed by reduction to provide the desired product (Scheme 51).…”
Section: Drugs For Central Nervous Diseasesmentioning
confidence: 99%
“…In Figure 3, the copolymers also exhibited the characteristic methine protons of NIPAM (g), the acidic protons of MAA (c), and ethoxy proton signals of CTA (i). The peak at 3.33 is due to the presence of moisture in DMSO-d 6 , which absorbs moisture very quickly during handling. Moreover, the IR absorptions illustrated in Figure 4 1 H NMR spectra of PNIPAM at 1717 and 1651 cm -1 can be attributed to the C=O stretchings of the carboxylic acid in MAA and the amide in NIPAM, respectively.…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…For example, Imatinib (Gleevec), a marketed anticancer drug, can be produced through microwave heating in five steps with shorter reaction times and higher yields than what can be obtained through traditional heating methods [5]. Various inhibitors and pharmaceutical molecules have been synthesized through microwave-assisted synthetic protocols to treat infectious diseases such as tuberculosis, HIV/AIDS, malaria, and hepatitis C [6][7][8][9]. Other notable examples, including biologically active heterocycles for Sildenafil analogs [10,11], nontoxic biofilm inhibitors (antimicrobial derivatives) [12,13], sirtuin 2-selective inhibitors [14,15], crosscoupling reactions [16,17], and positron emission tomography [18,19], have also been reported, and some reactions have been evaluated in a scale-up fashion [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…It is capable of improving product yields and enhancing the rate of reactions as well as being a safe and convenient method for heating reaction mixtures to elevated temperatures. Domestic microwave ovens are increasingly being replaced by scientific microwave apparatus for use in synthesis [1]. Microwave heating occurs on a molecular level as opposed to relying on convection currents and thermal conductivity when using conventional heating methods.…”
Section: Introductionmentioning
confidence: 99%